Tradisi Proses Mesbes Bangke (Mencabik Mayat) Di Banjar Buruan Kecamatan Tampaksiring Kabupaten Gianyar Bali - Ni Luh Ketut Sukarniti (Universitas Mahendradatta Denpasar, 2021)
The Mesbes Bangke tradition or shredding corpses in Bali. For those of you who are the first to hear or see how this tradition is being held, it will certainly make you amazed, because indeed the bodies of people who died (bangke) or corpses were torn apart by residents and only in Banjar Buruan, Tampaksiring, Gianyar Regency, Bali. So it is understandable for residents who do not know and are still unfamiliar with this tradition, of course it will seem strange and terrible. And of course there will be questions from you, Is there really a tradition of tearing corpses? Although this is a tradition that is certainly inherited from the ancestors, but this is an extreme tradition and is impossible for humans to carry out, is it possible that this can be carried out? The answer to all these questions is yes, this tradition can be said to be extreme, unique, rare and also activities that are not commonly carried out, let alone become a tradition.